An overview insight into employment of disabilities at workplace around the world - Nweiser, Mishlin; Dajnoki, Krisztina (Anali Ekonomskog fakulteta u Subotici, 2024)
Many people with disabilities still face difficulties and obstacles trying to secure employment. Organizations are becoming more and more aware that better vocational inclusion of people with disabilities (PWD) is in their best interests, due to factors such as a lack of skilled labor, an increase in the prevalence of disability among their aging workforces and altered societal attitudes and laws regarding the promotion of diversity and equity in the workplace. This article used a qualitative methodology and conducted a thorough evaluation of the existing literature using a variety of different databases such as Science Direct, Springer, Google Scholar, JSTOR, and Elsevier, which were used to identify various research articles related to the employment of PWD. We reviewed literature on the advantages of employing people with disabilities and also on HR management practices with regard to hiring people with disabilities, as well as investigating the methodology these literatures used. Our findings demonstrate that the benefits of hiring people with disabilities are many and bring several advantages. To better understand how benefits may differ by disability type, industry, and work type, more research is required.